Percepciones de los sistemas de trabajo de alto rendimiento e intención de marcha. Un análisis multinivel - Romina García Chas; Edelmira Neira Fontela; Concepción Varela Neira (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2012)
– Previous research on high-performance work systems (HPWSs) has primarily analyzed the effects of HPWSs on organizational performance from a management perspective. The current study distinguishes between management and employee perspectives of HPWS and examines how the two perspectives relate to engineers' intention to leave, using multilevel methodology. The results show significant differences between management and employee perspectives of HPWS and that the intended HPWS affects employees' intention to leave only through the employees' perceived HPWS.
Keywords: M12; 650; high performance work system; intention to leave; engineers